2001
DOI: 10.1007/s004200000206
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to airborne mercury during gold mining operations near El Callao, Venezuela

Abstract: The tasks with the highest mean airborne mercury exposures were "burning the mercury-gold amalgam" and "gold refining/smelting". Recommendations were provided for improving the retort design to better contain mercury, for ventilation in the gold shops, and for medical surveillance and educational programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 18 publications
3
37
0
1
Order By: Relevance
“…Similarly to previous studies [6,8,12,17], we found that participants who heated gold-mercury amalgams had elevated urine mercury concentrations compared with those who did not heat amalgams. This corresponds to what is known about mercury uptake in humans; very little elemental mercury is absorbed following dermal contact or ingestion while approximately 80 % of elemental mercury vapors that are inhaled are absorbed [23].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly to previous studies [6,8,12,17], we found that participants who heated gold-mercury amalgams had elevated urine mercury concentrations compared with those who did not heat amalgams. This corresponds to what is known about mercury uptake in humans; very little elemental mercury is absorbed following dermal contact or ingestion while approximately 80 % of elemental mercury vapors that are inhaled are absorbed [23].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, anyone who happens to be nearby can be exposed to mercury vapors when amalgams are heated. Given their potential to disperse mercury vapors throughout a wide area [12,17], it is likely that mercury inhalation via amalgam heating is the primary mercury exposure pathway in most Amazonian artisanal mining communities. Surprisingly, we found that urine total mercury and blood methylmercury concentrations were elevated in participants who drank water from wells, springs, and other nonpublic systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allthough Hg mining has been officially banned by local authorities in the province, some people continue to work illegally in the mercury (Hg) mine. These Hg mine workers are at a high risk of exposure to elemental mercury (Hg 0 ) vapor, particularly those engaged in smelting among the miners (1)(2)(3)(4)(5)(6)(7)(8). Moreover, such Hg mining operations is one of the primary source of environmental Hg pollution (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Mercury, being an active constituent of the Gold mining industry dates back to the 16 th century. Mercury is used in amalgamation and concentration of gold and thus is a major source of contamination in developing countries (Rojas et al 2001). 4 The release of mercury in the biosphere is said to have exceeded 260,000 tons between the year 1550 and 1930, brought about due to gold mining procedures (Lacerda 1997) 5 .…”
Section: Introductionmentioning
confidence: 99%